Standardized protocol and outcome measurements for the collagen antibody-induced arthritis mouse model - Tazio Maleitzke; Jérôme Weber; Alexander Hildebrandt; Tamara Dietrich; Sijia Zhou; Serafeim Tsitsilonis; Johannes Keller (STAR Protocols, 2022)
Summary: The murine collagen antibody-induced arthritis (CAIA) model resembles various features of human rheumatoid arthritis and is based on the intraperitoneal or intravenous injection of autoantibodies against type II collagen. Here, we present a standardized protocol for the intraperitoneal injection of arthritis-inducing autoantibodies in mice, followed by a description of daily arthritis assessments. We then detail the steps to harvest joint and bone tissues for histological, radiological, and molecular analyses. We highlight animal welfare and 3R considerations for experimental arthritis studies.For complete details on the use and execution of this protocol, please refer to Maleitzke et al. (2021, 2022). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.